Clinical outcomes with low dose anti-thymocyte globulin in patients undergoing matched unrelated donor allogeneic hematopoietic cell transplantation. Issue 8 (2nd July 2020) - Mountjoy, Luke; Jain, Tania; Kunze, Katie L.; Khera, Nandita; Sproat, Lisa Z.; Jennifer, Woodburn; McCallen, Margaret; Leis, Jose F.; Noel, Pierre; Slack, James L.; Palmer, Jeanne
Abstract: Anti-thymocyte globulin (ATG) has been associated with decreased rates graft versus host disease (GVHD) but with a potential risk of increasing risk of infection and relapse. We retrospectively studied the impact of single dose low dose (2.5 mg/kg) ATG in patients undergoing allogenic hematopoietic cell transplantation (HCT) from 8/8 matched unrelated donors (MUD). Of the total 209 patients identified, 129 received ATG. At baseline, the ATG group had more intermediate and high disease risk index (DRI) (64.6% vs. 54.3%) (28.3% vs. 23.7%) p  < .001, respectively, and who received reduced intensity or non-myeloablative conditioning (RIC) (69.0% vs. 47.5%, p .003). There was no significant difference in the overall survival (OS) HR = 1.3, 95% CI [0.99, 1.0], p  = .350 or relapse-free survival (RFS) HR = 1.2, 95% CI [0.74, 1.8], p  = .526 between the two groups. Patients receiving ATG had a lower incidence of chronic GVHD (cGVHD) (10.1% vs. 25%, p  = .007) and less moderate to severe cGVHD (8.5% vs. 25%, p  = .002). ATG was associated with a reduced incidence of moderate to severe cGVHD OR = 0.28, 95% CI [0.12, 0.61], p  < .01. There was no difference in the incidence of Epstein-Barr Virus (EBV) or cytomegalovirus (CMV) reactivation, CMV disease, invasive fungal infection, or grade III–IV acute GVHD (aGVHD). Our study shows that low dose ATG results in similar OS and RFS with lower rates of cGVHD. Additional prospective studies are needed to confirm these findings.